Somatic mutations in specific and connected subpathways are associated with short neuroblastoma patients' survival and indicate proteins targetable at onset of disease. Issue 10 (17th September 2018) - Esposito, Maria Rosaria; Binatti, Andrea; Pantile, Marcella; Coppe, Alessandro; Mazzocco, Katia; Longo, Luca; Capasso, Mario; Lasorsa, Vito Alessandro; Luksch, Roberto; Bortoluzzi, Stefania; Tonini, Gian Paolo
Abstract : Neuroblastoma (NB) is an embryonic malignancy of the sympathetic nervous system with heterogeneous biological, morphological, genetic and clinical characteristics. Although genomic studies revealed the specific biological features of NB pathogenesis useful for new therapeutic approaches, the improvement of high‐risk (HR)‐NB patients overall survival remains unsatisfactory. To further clarify the biological basis of disease aggressiveness, we used whole‐exome sequencing to examine the genomic landscape of HR‐NB patients at stage M with short survival (SS) and long survival (LS). Only a few genes, including SMARCA4, SMO, ZNF44 and CHD2, were recurrently and specifically mutated in the SS group, confirming the low recurrence of common mutations in this tumor. A systems biology approach revealed that in the two patient groups, mutations occurred in different pathways. Mutated genes ( ARHGEF11, CACNA1G, FGF4, PTPRA, PTK2, ANK3, SMO, NTNG2, VCL and NID2 ) regulate the MAPK pathway associated with the organization of the extracellular matrix, cell motility through PTK2 signaling and matrix metalloproteinase activity. Moreover, we detected mutations in LAMA2, PTK2, LAMA4, and MMP14 genes, impairing MET signaling, in SFI1 and CHD2 involved in centrosome maturation and chromosome remodeling, in AK7 and SPTLC2, which regulate the metabolism of nucleotides and lipoproteins, and in NALCN, SLC12A1, SLC9A9, which are involved in the transport of small molecules. Notably, connected networks of somatically mutated genes specific for SS patients were identified. The detection of mutated genes present at the onset of disease may help to address an early treatment of HR‐NB patients using FDA‐approved compounds targeting the deregulated pathways. Abstract : What's new? Most patients with metastatic neuroblastoma don't survive 5 years from diagnosis, despite responding well to first‐line treatments. Previous work comparing short‐survival and long‐survival patients identified some key chromosomal differences. These authors take the search deeper, conducting whole‐exome sequencing to compare somatic mutations between patients who survived at least 5 years and those who did not. They determined that mutations among the short‐survival group affected different pathways than those afflicting the long‐survival patients. In some cases, drugs already exist that target these proteins, suggesting that testing for these mutations at the time of diagnosis could indicate specific treatments.